2022
DOI: 10.1002/jmri.28145
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinal Muscle in Chronic Low Back Pain: Comparison Between Standard Parameters and Chemical Shift Encoding‐Based Water–Fat MRI

Abstract: Background Paraspinal musculature (PSM) is increasingly recognized as a contributor to low back pain (LBP), but with conventional MRI sequences, assessment is limited. Chemical shift encoding‐based water–fat MRI (CSE‐MRI) enables the measurement of PSM fat fraction (FF), which may assist investigations of chronic LBP. Purpose To investigate associations between PSM parameters from conventional MRI and CSE‐MRI and between PSM parameters and pain. Study Type Prospective, cross‐sectional. Population Eighty‐four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In addition to the fat quantification of vertebral BM, the CSE-MRI-derived PDFF has recently also been used to evaluate paraspinal muscle fat content [ 14 , 15 , 16 ]. For the degenerative spine, it has been shown that paraspinal muscle PDFF may be associated with lumbar back pain (LBP) and that cartilage endplate damage could be predictive of LBP when adjacent to paraspinal muscles with higher fat content [ 14 , 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the fat quantification of vertebral BM, the CSE-MRI-derived PDFF has recently also been used to evaluate paraspinal muscle fat content [ 14 , 15 , 16 ]. For the degenerative spine, it has been shown that paraspinal muscle PDFF may be associated with lumbar back pain (LBP) and that cartilage endplate damage could be predictive of LBP when adjacent to paraspinal muscles with higher fat content [ 14 , 15 ].…”
mentioning
confidence: 99%
“…In addition to the fat quantification of vertebral BM, the CSE-MRI-derived PDFF has recently also been used to evaluate paraspinal muscle fat content [ 14 , 15 , 16 ]. For the degenerative spine, it has been shown that paraspinal muscle PDFF may be associated with lumbar back pain (LBP) and that cartilage endplate damage could be predictive of LBP when adjacent to paraspinal muscles with higher fat content [ 14 , 15 ]. Furthermore, anatomical variations in PDFF for paraspinal muscles have been explored in relation to gender and body mass index (BMI), demonstrating associations for PDFF values between segments of the erector spinae muscles at the lower thoracic and lumbar spine (T9-T11, T12-L2, and L3-L5) [ 16 ].…”
mentioning
confidence: 99%
“…In this issue of JMRI , the manuscript by Sollmann et al investigated the utility of chemical shift encoding‐based water–fat MRI (CSE‐MRI) in quantifying the fat fraction (FF) within the paraspinal musculature in 84 adults with chronic lower back pain 3 . The study is part of the greater Back Pain Consortium Research Program which aims at developing effective and personalized care for lower back pain patients 3 …”
mentioning
confidence: 99%
“…CSE‐MRI is a common multiecho (in‐phase and out‐of‐phase) sequence that capitalizes on the different precessional frequencies of fat and water in the tissue and can produce homogeneous fat‐specific images. The resulting proton density FF maps can be used to directly quantify the amount of fat in a prespecified region of interest such as the rotator cuff or erector spinae muscles 3,4 . The MRI protocol in this study consisted of a T1‐weighted fast spin‐echo and a six‐point iterative decomposition of water and fat with echo asymmetry and least‐squares estimation (IDEAL) sequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation